The Effectiveness of the School Literacy Program in Enhancing Students’ Reading Interest at SMK Negeri 1 Mempawah Hilir - Afifah Siti Nur Baiti; Firmansyah Firmansyah; M. Saprawi Rizal (PT Barkah Ilmi Fiddunya, 2026)
This study aims to analyze the implementation strategies and the level of effectiveness of the School Literacy Program (SLP) in improving students’ reading interest at SMK Negeri 1 Mempawah Hilir. The study employs a qualitative approach with a descriptive design. Data were collected through interviews, observations, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that the School Literacy Program is designed in a contextual and adaptive manner in accordance with the characteristics of vocational high school students. The main strategies implemented include a 15-minute reading habit before class, literacy journal writing, reading discussions, and the provision of reading corners in each classroom. The implementation of these strategies has been shown to increase students’ active participation, reading independence, positive attitudes toward literacy, and their ability to produce written works such as short stories and poetry. However, the program’s effectiveness has not yet been optimal, as some students are still not fully engaged. The novelty of this study lies in revealing a contextual-adaptive literacy implementation model in the vocational school setting, which integrates habituation, reflection, and creative production as a unified strategy to enhance students’ reading interest.